Alcohol‐Selective Oxidation in Water under Mild Conditions via a Novel Approach to Hybrid Composite Photocatalysts. Issue 6 (14th July 2015) - Abd‐Elaal, Ali; Parrino, Francesco; Ciriminna, Rosaria; Loddo, Vittorio; Palmisano, Leonardo; Pagliaro, Mario
Abstract: The oxidation of alcohols to carbonyl compounds in a clean fashion (i.e., with water as a solvent or under solvent‐free conditions, and using O2 or H2 O2 as the primary oxidant) is the subject of considerable research efforts. A new approach for the selective oxidation of soluble aromatic alcohols in water under mild conditions via a novel composite photocatalyst has been developed. The catalyst is synthesized by grafting 4‐(4‐(4‐hydroxyphenylimino)cyclohexa‐2, 5dienylideneamino)phenol and silver nanoparticles onto the surface of moderately crystalline titanium dioxide. The titanium dioxide‐based composite was first extensively characterized and then employed in the catalytic oxidation of 4‐methoxybenzyl alcohol to 4‐methoxybenzaldehyde under UV irradiation in water at room temperature. The corresponding aldehyde was obtained with unprecedented high selectivity (up to 86 %). The method is general and opens the route to fabrication of photocatalytic composites based on titanium dioxide functionalized with shuttle organic molecules and metal nanoparticles for a variety of oxidative conversions. Abstract : A new approach for the selective oxidation of soluble aromatic alcohols in water under mild conditions via a novel composite photocatalyst has been developed. The catalyst is synthesized by grafting an organic diol and silver nanoparticles onto the surface of titanium dioxide. The method is general and opens the route to optimization of the selective conversion for several other photocatalytic redox reactions mediated by similar advanced hybrid composites.